Management of accessory parotid gland tumours: 32-year experience from a single institution and review of the literature. Issue 9 (September 2019) - Luksic, I.; Mamic, M.; Suton, P.
Abstract: Accessory parotid gland tumours (APGTs) are very rare. Regarding their anatomical location, an adequate surgical approach is necessary to provide safe resection and satisfactory postoperative results. The aims of this study were to present our tertiary centre experience in surgical treatment and management of APGTs and to review the literature regarding their treatment, particularly in terms of surgical modalities. Data of 13 patients with primarily surgically treated APGTs have been collected and analysed. Well-documented English-literature articles of surgically treated APGTs have been extracted from the PubMed, Scopus and Web of Science databases ending in May 2018, and analysed. Mean age at diagnosis was 41.1 years. The most common benign histological subtype was pleomorphic adenoma (53.8%), while mucoepidermoid carcinoma (23.1%) was most common in malignant counterparts. The malignancy rate was 38.5%. Postoperative results were satisfactory, and the follow-up period was uneventful in all patients except one who died of locoregional recurrence. A total of 57 papers with reported series in APGTs have been identified with a total of 306 APGT cases. From oncological, functional and aesthetic standpoints, approaches through a standard parotidectomy provide satisfactory results.